ANALISIS FAKTOR KOMUNIKASI TERHADAP PENGAMBILAN KEPUTUSAN PADA KECAMATAN TANJUNGBALAI UTARA - Gunawan Adiputra Munthe; Wulan Wardaningtias Putrini; Nurmala Siregar; Riski Anggita Akbar Sagala; Nur Ainun harahap (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2021)
This research discusses about the influences of perception, emotion, and knowledge as communication factors on decision making at North Tanjungbalai District. The aim of this research is to analyse the influences of perception, emotion, and knowledge both partially and simultaneously on decision making at the office. This is  a quantitative research with random sampling technique. The sample is 44 employees. Results show that each independent variable; perception, emotion, and knowledge, partially influences decision making positively and significantly. perception has tcount  value 2,578   and level of significance 0.016, emotion   has   3,200   and   0.004,   and   knowledge   has   4,201   and   0.000. Simultaneously, perception, emotion, and knowledge have significant and positive influences on decision making at North Tanjungbalai District with Fcount  value 19,355 and level of significance 0.000.